Human papillomavirus infections in women with and without squamous cell abnormalities of the uterine cervix - Dabeski, Drage (Scripta Medica, 2019)
Introduction: Human papillomavirus infections are one of the most common sexually transmitted infections with viral etiology. Aim of the study: The aim of the study was to confirm the existence of an association between human papillomavirus infection and squamous cell abnormalities of the uterine cervix. Material and Methods: Cohort study, conducted in the period from January 2017 to June 2018 of 768 sexually active women, age groups of 20 to 59 years, divided into two groups: examined and control, who came to their annual gynecological exam at University Clinic for Gynecology and Obstetrics in Skopje. In all patients was done human papillomavirus-deoxyribonucleic testing. Human papillomavirus detection and typing was done using a polymerase chain reaction and reverse hybridization. Results: Data analysis showed an association between human papillomavirus infection and squamous cell abnormalities of the uterine cervix (p=0.00001). Human papillomavirus infection was detected in 22.91% of all patients, in 75.00% of patients with abnormal cervical cytology and in 12.50% of patients with normal cervical cytology. A single human papillomavirus infection was detected in 13.67% of all patients (in 59.66% of human papillomavirus positive patients). Mixed human papillomavirus infection was detected in 9.24% of all patients (in 40.34% of human papillomavirus positive patients). Human papillomavirus type 16 was the most common genotype with 40.91%. Conclusion: Our study confirmed that there is an association between human papillomavirus infection and squamous cell abnormalities of the uterine cervix and the young population under the age of 30 years is the most affected. Keywords: human papillomavirus, squamous cell abnormalities, uterine cervix